2012
DOI: 10.1002/jcb.23446
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of HIV‐1 Tat on the survival and differentiation of vessel wall‐derived mesenchymal stem cells

Abstract: HIV infection is an independent risk factor for atherosclerosis development and cardiovascular damage. As vessel wall mesenchymal stem cells (MSCs) are involved in the regulation of vessel structure homeostasis, we investigated the role of Tat, a key factor in HIV replication and pathogenesis, in MSC survival and differentiation. The survival of subconfluent MSCs was impaired when Tat was added at high concentrations (200-1,000 ng/ml), whereas lower Tat concentrations (1-100 ng/ml) did not promote apoptosis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In our study CVD risk was assessed by SCORE scale, and we found that in the group with MS the percentage of patients with very high risk was five times as high as in the group without MS, and the percentage of patients with low risk was two-times lower in the group with MS than in the group without MS. Tat, a crucial molecule in the HIV replication process, can affect mesenchymal stem cell survival and differentiation, and this might play an important role in vessel damage and formation of atherosclerotic lesions in HIV-infected individuals [28].…”
Section: Discussionmentioning
confidence: 99%
“…In our study CVD risk was assessed by SCORE scale, and we found that in the group with MS the percentage of patients with very high risk was five times as high as in the group without MS, and the percentage of patients with low risk was two-times lower in the group with MS than in the group without MS. Tat, a crucial molecule in the HIV replication process, can affect mesenchymal stem cell survival and differentiation, and this might play an important role in vessel damage and formation of atherosclerotic lesions in HIV-infected individuals [28].…”
Section: Discussionmentioning
confidence: 99%
“…We believe, however, that in HIV-positive individuals, apoptosis may also be related to HIV per se. For example, HIV-related proteins such as tat and gp120 may induce apoptosis in human brain microvascular endothelial cells, arterial-wall derived mesenchymal cells (including myocytes), and blood cells [15,16]. Evidence exists that HIV may infect smooth muscle cells in coronary arteries, and although evidence of such infection has not been produced in brain arteries, the higher intensity of staining for caspase 3 among those with protracted immunosuppression and lower nadir CD4 + T-cell count in this sample suggests that persistent immunosuppression may enable or perpetuate arterial wall infection and trigger apoptosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Further study found that Tat stimulated upregulation of intercellular cell adhesion molecules specifically ICAM-1 in HUVECs was through the suppression of miR-221/-222 in a NF-κB-dependent pathway [ 48 ]. Tat-related impairment of the survival and differentiation of mesenchymal stem cells might play an important role in vessel damage and formation of the atherosclerotic lesions observed in HIV-infected patients and this could be considered an additional important mechanism involved in promoting vascular damage and atherosclerosis in the course of HIV disease [ 49 ]. In addition, Tat could mediate the induction of adhesion molecules and also function as an exogenous cytokine in the activation of human endothelial cells, which upregulates E-selectin expression, enhances the secretion of IL-6, and synergizes with TNF in mediating these effects [ 50 ].…”
Section: Hiv Tat and Cardiovascular Diseasesmentioning
confidence: 99%